Risk Analysis in a General Warehouse using IEC 31010 Guidelines - Udomsin, Warrasade; Prasertpornsri, Kittichai; Arunreang, Manthanaporn (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2024)
The complexity, volatility, interconnectedness of systems, technology, and size of the supply chain bring about problems and risks associated with finance, reliability, environmental impact, failed strategies, etc. The mechanism to systematically analyze problems and risks will help executives or operators make decisions about risks correctly and responsibly for the organization. This article presents a risk assessment method (6 processes) and risk assessment tools from the British Standards Institution (BSI) to analyze and explain. A case study of a warehouse with sunk cost problems is used, employing cause-and-effect diagrams and Bow-shaped analysis diagrams. It was found that sunk costs were caused by inventory reserve, raw materials deterioration, incorrect counting of raw materials and products, and demand forecasts that are often wrong, which affects reduced cash flow and increased opportunity costs. The approach to solving the problem is to develop a database system, design new processes, set order quantity, track raw materials and products, find new funding, and find partners to produce certain products, respectively.